Discoveries and Dangers in Teaching Theology with PowerPoint - Pauw, Amy Plantinga (Teaching theology and religion, 2002)
PowerPoint can be a genuine aid to theological education by providing a medium for employing visual art in the classroom. But PowerPoint does not and should not replace the ordinary stuff of teaching and learning theology: reading, lecturing, discussing texts, and writing papers. Like any other tool, its pedagogical benefit depends on discerning use. Particular care must be used to blunt PowerPoint's tendency to produce a disembodied, decontextualized learning environment. Using PowerPoint to incorporate art into theology classes is not merely a strategy for making verbal points more powerfully. Art can sometimes go where theological words cannot.